Nursing performance in preventing and reducing diabetic nephropathy in primary health care (Research, Society and Development, 2020)
The objective of this study is to describe, according to the existing literature, nursing actions aimed at preventing and reducing the progression of DiabeticNephropathy (DN) in Primary Health Care. It is na integrative literature review, of a descriptive nature, with a qualitative approach. Data collected from August to September 2020, using a protocol based on the PICo strategy. Controlled descriptors and keywords were used, crossed with Boolean operators OR and AND, in the Virtual Health Library (VHL), SciELOand Google Scholar platforms. The final products were 13 studies classified by similarity and grouped by similar themes, which generated 2 categories: "Preventive measures of DiabeticNephropathy" and "Measures that reduce the progression of Diabetic Nephropathy". Nursing interventions are aimed at patient and family education, training of the nursing team, control of arterial hypertension, hyperglycemia and other aggravating factors, metabolic control through laboratory tests and multiprofessional care, all with a positive impact on the effective treatment of Diabetes Mellitus (DM) and maintenance of renal function. With this study it was observed that nursing has reduced scientific production on the subject, as well as educational activities and other procedures are centered on renal comorbidities when already installed in diabetic patients, leaving their prevention devalued. In addition, further research is needed to assess current treatments, new ways for family and patient involvement in disease prevention, as well as those aimed at implementing updated and unified protocols for all PHC units.